Clarion call to maintain environmental flows to protect Nepal’s rivers - KC, Jibesh; Phuyal, Surendra (International Water Management Institute, 2024)
Two workshops organized by IWMI in August 2024 highlighted the need for renewed efforts to ensure adequate e-flows to protect the health of rivers in Nepal. There is growing concern that most hydroelectric dams undermine regulations requiring a minimum 10 percent e-flow to sustain local ecosystems.